Pengaruh Latihan Footwork dan Lari Bolak Balik Terhadap Kelincahan pada Pemain Bulu Tangkis Pemula - Dwi Yuni Kantari; Soemardiawan Soemardiawan; Aminullah Aminullah (Universitas Hamzanwadi, 2026)
The problem addressed in this study is the low level of agility among beginner badminton players at Mataram State High School 9, as evidenced by their slow movements when reaching for the shuttlecock, slow positional shifts, and a physical training program that is not yet optimized. The purpose of this study was to examine the effect of footwork and shuttle run training on improving the agility of beginner badminton players, compared to a control group that did not receive any special treatment. The method used was a quantitative experiment with a two-group pretest-posttest design. The sample consisted of 14 male students. The instrument used was the Illinois Agility Test (IAT) with a reliability coefficient (ICC) of 0.931. Training was conducted three times per week for six weeks, with intensity measured using the Borg RPE scale. The results showed that the experimental group experienced a decrease in average completion time of 2.43 seconds (a 12.24% improvement), while the control group experienced a decrease of only 0.36 seconds (1.81%). Hypothesis testing confirmed a significant effect in the experimental group, with a calculated t-value (10.43) > table t-value (2.447) and a p-value of 0.000 < 0.05. The experimental group improved its agility category from “Regular” to “Excellent” based on IAT norms, whereas the control group remained in the “Regular” category. The conclusion of this study is that footwork and shuttle run exercises have a significant effect on improving the agility of beginner badminton players.